Ecocide Activities and Oil Firms’ Ecological Marketing Practice: A Focus on Agricultural-Economic Sustainability in Niger Delta - Loanyie, Komene, Goodnews (World Journal of Business and Management, 2024)
This study was carried out to examine the extent to which the ecocide activities in Niger Delta have affected the ecological marketing practices of the oil firms: Shell BP, Agip Oil Company, and Elf Oil Company in the improvement of the agricultural economic wellbeing of the oil-bearing communities in Niger Delta. A descriptive survey research design was employed in this study. The population of the study was 37,965,391 drawn from Niger Delta States based on which a sample size of 400 respondents was determined using Taro Yamane’s sample size determination techniques at 0.5 percent level of significance. The purposive sampling procedure was employed to enable the researcher to select the representative sample elements of the population interest from the right respondents who have adequate knowledge of the study under investigation from the different strata that makes up the population of the study. A structured instrument for data collection containing twenty (20) item questions was used for the study. The face and content validation of the instrument was obtained through the judgment of experts. A test-retest method was used to determine the reliability of the instrument and the reliability index of .83 was obtained. The data collected for the study were analyzed using the mean score test and the percentage test method to answered the research questions; while the inferential statistics of the Z-score test was used to test the null hypothesis at .05 level of significance. Results obtained revealed that “Ecological marketing practice of the oil firms does not significantly improved agricultural economic poverty, agricultural market failure, agricultural economic frustration, and agricultural land limitation in the oil-bearing communities in Niger Delta”. The implication of this finding is that the oil firm’s ecological sustainability marketing activities was considered to lack the needed proactive improvement values which, if ethical based ecological effort is not adopted to create sustainable improvement; oil firms might experience unpredicted operational interruption by the oil-bearing communities. It was therefore, recommended that oil firms should consider employing proactive ecological marketing efforts in a more ethical and responsible manner to sustain the agricultural economic wellbeing of the oil-bearing communities.